EFFECTS OF THE SEAWEED EXTRACT OF GRACILARIA EDULIS ON THE GROWTH OF ZEA MAYS L. IN A GREENHOUSE - Mol. S, Reena (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The application of marine macroalgae-based biostimulants has gained increased momentum in terms of plant growth and crop production. Seaweed has biostimulatory activities that result in improved plant growth and crop growth in various important commercial crops. They contribute to resistance to various abiotic and biotic stresses. In the present study, Gracilaria edulis was collected from the west coast of India. The compositions of fibre, protein, carbohydrate, moisture, ash, vitamins and other minerals were determined. The biostimulant properties of the seaweed extract were tested on Zea mays L. in a greenhouse. Z. mays L. seedlings were treated with seaweed extracts (0.5%, 1%), 1.5%, or 2.0%). The seaweed extract improved the elemental composition and chlorophyll content of the leaves. These findings revealed that seaweed extracts are suitable for environmentally friendly crop management.